Problematika Pengembangan Kepribadian Guru di SD Muhammadiyah Bendo Kalibawang Kulon Progo, DIY - Afifah, Rosyidatul; Rahmawati, Heni; Aulia Inayah, Risma; Husna, Difa’ul (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2021)
This study aims to determine the problems in the personality development of teachers at SD Muhammadiyah Bendo Kalibawang Kulon Progo. The approach used is a descriptive qualitative approach. The focus of this research is the problems faced by teachers in the development of personality competencies in schools. The subjects of this study were principals and teachers at SD Muhammadiyah Bendo Kalibawang Kulon Progo. Methods in data collection using documentation and interviews with principals and teachers at SD Muhammadiyah Bendo Kalibawang Kulon Progo. Documentation techniques are used to find data on matters in the form of transcripts, notes, newspapers, books, meeting minutes, and others. Meanwhile, interviews were conducted to explore verbal or qualitative data obtained from key informant sources. The results showed that the problems faced by teachers in personality development at SD Muhammadiyah Bendo Kalibawang Kulon Progo are because they are still carried by their personalities from birth. In addition, lack of confidence in expressing opinions, lack of time discipline, lack of appreciation for student work, and difficulty separating problems at home and school are also problems in teacher personality development. Based on this research, it can be concluded that the problematic personality development of teachers at SD Muhammadiyah Bendo Kalibawang can be improved by evaluation and coaching so that the personality competence of teachers who are responsible, authoritative, mature, stable and others can be obtained.